HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG ANEMIA DEFISIENSI BESI DENGAN KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET TAMBAH DARAH DI PUSKESMAS TARUS KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Lalo, Vani; Parera, Juliana Alda; Rambu Podu, Christin Inriati; Yulianti, Hasri; Mamoh, Kamilus; Huru, Matje Meriaty; Awang, Mariana Ngundju; Abuk Seran, Agustina (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Anemia in pregnancy is a condition in which a mother has a hemoglobin level of less than 11 grams per deciliter of blood at 0-12 weeks gestation and at 25 to 42 weeks gestation, or hemoglobin levels less than 10.5 grams per deciliter of blood at 13 to 24 weeks gestation. One of the causes of maternal death is iron deficiency anemia in pregnant women which can cause complications in pregnancy(Teja et al., 2021). The impact of iron deficiency anemia on pregnant women is 12%-28% fetal mortality, 30% perinatal mortality and 7%-10% neonatal mortality rate. Efforts made to prevent and overcome anemia in pregnant women are to give blood tablets. This study aims to determine the relationship between pregnant women’s knowledge about iron deficiency anemia with the compliance of pregnant women in taking blood-added tablets. This study used an observational analytical design with an approach Cross Sectional. The population in this study is all pregnant women who checked their wombs at the Tarus Health Center for the period April-July 2023. The sampling technique is Purposive Sampling. Analysis with test Chi-Square by using SPSS 25 for Windows. The results showed a significant relationship between the knowledge of pregnant women about iron deficiency anemia with the compliance of pregnant women taking iron tablets in pregnant women with a p value = 0.017 (p < 0.05). Conclusion: There is a significant relationship between the knowledge of pregnant women about iron deficiency anemia with the compliance of pregnant women to consume blood-added tablets in pregnant women.